Public-Private Partnership in Germany and Tunisia. - (:unkn) unknown (BWV Berliner Wissenschaftsverl., 2016)
Public-Private Partnership models are often controversially discussed with regard to not only their benefits and advantages, but also the chances and risks inherent in their realisation. However, there is no doubt that in developing countries the involvement of private investment and private partner can contribute to economic growth and the expansion of infrastructure. In Tunisia, the government is actively supporting PPP projects, believing that they are crucial for the further development of the country s economy and the welfare of the people. The contributions in this book are the result of the cooperation between Tunisian and German scholars and reflect general as well as country-specific current and future frameworks of PPP and best practices of both countries. A comparison of Tunisia s concession-based concept with the infrastructure- and construction-focused approach in Germany leads to the conclusion that an open framework for PPP is desirable. The volume provides not only scholars, but also policymakers in Maghreb countries and development and investment protagonists with an overview of the PPP sector s current development in Tunisia and Germany.
Keywords: Verwaltung; Marktwirtschaft; Unternehmen; Kooperation; Finanzierungsmodell; Beschaffung; Rechnungswesen; Kosten-Nutzen-Analyse; Öffentliches Recht; Wirtschaftsrecht; Public-Private-Partnership; Internationaler Vergleich